Physical Principles of Electron Microscopy An Introduction to TEM, SEM, and AEM - Egerton, R.F (Springer International Publishing : Imprint: Springer, 2016)
This popular textbook provides an introduction to the theory and practice of electron microscopy. The second edition has been updated to reflect the recent developments, including correction of lens aberrations in a TEM column and new material on environmental TEM and SEM. The text is linked to a new website that contains additional educational material such as sample exam questions and answers to selected problems. This edition also contains expanded reference lists that allow the reader to efficiently explore key topics in greater depth. Scanning and fixed-beam electron microscopes are an indispensable tool for both research and routine evaluation in the physical, biological and medical sciences, including specialized fields in materials science, nanotechnology and semiconductor processing. Physical Principles of Electron Microscopy, Second Edition, is ideal for students, researchers, and technologists who make use of electron microscopes but haveonly a limited knowledge of physics and mathematics. Undergraduate students will understand how basic principles of physics are utilized in this important area of applied science, while university teachers and researchers will find a concise but authoritative teaching, supplemental, or reference text covering the basic principles and practice of microscopy.